2012
DOI: 10.3109/09513590.2011.652719
|View full text |Cite
|
Sign up to set email alerts
|

High plasma level of long Pentraxin 3 is associated with insulin resistance in women with polycystic ovary syndrome

Abstract: PTX3 level is increased in patients with PCOS in concordance with insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
1
22
3
Order By: Relevance
“…PTX3 is present in atherosclerotic lesions and in small-vessel vasculitis in humans [22,30]. Aydogdu et al [31] investigated the association between PTX3 levels and insulin resistance in patients with polycystic ovarian syndrome. They found increased plasma PTX3 levels in women with polycystic ovarian syndrome compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…PTX3 is present in atherosclerotic lesions and in small-vessel vasculitis in humans [22,30]. Aydogdu et al [31] investigated the association between PTX3 levels and insulin resistance in patients with polycystic ovarian syndrome. They found increased plasma PTX3 levels in women with polycystic ovarian syndrome compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown high PTX3 levels are associated with unstable angina [13], adverse outcomes after myocardial infarction [14] and heart failure [15], and suggested PTX3 as a prognostic marker for CVD. In the literature there is only one study investigating the PTX3 levels in PCOS and they found higher PTX3 levels in the PCOS group than control group (1.0 ± 3.6 vs. 0.8 ± 0.3, p = 0.021) [16]. Although the groups had a similar number and the diagnosis of PCOS was made with the same criteria (ESHRE/ASRM Rotterdam), in the present study we found no difference in the PCOS and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, PTX3 levels were higher in women with PCOS, but these did not reach statistical significance (1.44 ± 1.62 vs. 1.16 ± 0.87, p = 0.927). Furthermore, Aydoğdu et al [16] reported that PTX3 levels were correlated positively with BMI, WHR, hs-CRP and HOMA-IR (p < 0.05 for all). Similarly in the present study we found a positive correlation between PTX3 and weight, BMI, IR, and HOMA-IR.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only one recent study, carried out by Aydogdu et al (15), previously assessed PTX3 levels in PCOS women. Unlike in our findings, in this study PTX3 concentrations were slightly higher in PCOS subjects and correlated directly with HOMA-index and serum CRP, and inversely with HDL-cholesterol.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%